EP1222 Is conservative surgery appropriate in ovarian granulosa cell tumors with tumor rupture?. (1st November 2019) - Gouy, S; Miailhe, G; Gauthier, H; Pautier, P; Maulard, A; Genestie, C; Morice, P; Leary, A
Abstract : Introduction/Background: To evaluate oncological and fertility outcomes after conservative surgery for ovarian granulosa cell tumors (GCT) associated with tumor rupture. Methodology: Retrospective study of patients (pts) <40 years, referred to our center with a GCT, who were treated with conservative surgery (contralateral ovarian and uterine preservation) and stages IC 1 and 2 according to the 2014 FIGO classification. Results: Sixteen patients were identified (adult GCT 11 pts, juvenile GCT 5 pts); median age was 27 [19–40] years. Nine patients had stage IC1 (54%) and 7 (44%) stage IC2. Eight (50%) patients received adjuvant chemotherapy with bleomycin, etoposide and cisplatin (PEB). With a median follow up of 9.2 [0.7–31] years, the relapse rate was high at 68% (11/16) with a median delay of 4.5 [0.6–19.6] years. The locations of relapse were pure peritoneal (n=8), contralateral ovary + peritoneal (n=2), contralateral ovary + peritoneal+ liver metastasis (N=1). Amongst these 16 patients, 11 were in remission, 3 were alive with disease and 2 died due to disease (in 2 juvenile types). Of the 11 patients with an adult GCT, 5 received adjuvant chemotherapy and 8 relapsed. Two (40%) relapsed in the adjuvant chemotherapy group whilst all of the 6 (100%) without adjuvant chemotherapy relapsed. Four patients had a pregnancy. Conclusion: For adult GCT, conservative surgery followed by adjuvant chemotherapy with PEB as an alternative after complete surgical staging for ICs who desire fertility preservation. Completion surgery should be done after childbearing or after an age which remains to be defined (potentially at 40 years old) in order to reduce the risk of relapse. For juvenile GCT in young adults we are unable to recommend the same strategy due to the lack of data. Disclosure: Nothing to disclose.